A Review of Structural Relationships in Closed-Loop Supply Chain Model - E Yuliawati; Pratikto Pratikto; Sugiono Sugiono; O Novareza (Institut Teknologi Sepuluh Nopember, 2018)
The acquisition strategy of returned products has become essential in the study of reverse supply chain. There are three primary activities included in the process of a the reverse supply chain, the acquisition of returned products, the remanufacturing process, and redistribution. This literature review intends to study the existing relationship amongst supply chain players in a closed-loop supply chain (CLSC) model. In the remanufacturing process performed by the company, returned products must be collected from consumers. Therefore, remanufacturing companies rely upon consumers as cores suppliers. This makes the good relationship between the two become crucial in company operational sustainability successfully. In this study, the identified journal articles were categorized into types of structural relationships between supply chain players and network structures of a reverse supply chain. Types of structural relationships are ownership-based, service-contract, direct-order, deposit-based, credit-based, buy-back, and voluntary–based. There are four types of returned product collector and remanufacturer: Original Equipment Manufacturer (OEM), a third party (3PL), retailer, and remanufacturer. Discussion of the journal articles was presented in each category. After that, the structural relationship was explored to find its advantage and disadvantage, so that CLSC can be managed effectively and efficiently. As a summary, suggestions for future research were described as the result of the literature review conducted.